Benefits of group compassion-focused therapy for treatment-resistant depression: A pilot randomized controlled trial - Asano, Kenichi; Tsuchiya, Masao; Okamoto, Yoko; Ohtani, Toshiyuki; Sensui, Toshihiko; Masuyama, Akihiro; Isato, Ayako; Shoji, Masami; Shiraishi, Tetsuya; Shimizu, Eiji; Irons, Chris; Gilbert, Paul (Frontiers in Psychology, 2022)
Major depression is one of the most common mental health problems worlwide. More than one-third of patients suffer from treatment-resistant depression (TRD). In this study, we explored the feasibility and acceptability of group compassion-focused therapy (CFT) for TRD using a randomized controlled trial with two parallel groups. Eighteen participants were randomly allocated to the intervention group (CFT and usual care) and control group (usual care alone). Participants in the intervention group received a 1.5-hour session every week for 12 weeks. The effects of the intervention on the participants’ scores were calculated using a linear mixed model. There was a larger reduction in their depressive symptoms and fears of compassion for self and a greater increase in their compassion for self compared to the control group participants. The reliable clinical indices showed that in the CFT (intervention) group, three of nine participants recovered (33%), two improved (22%), two recovered but non-reliably (22%), and the condition of two remained unchanged (22%). These findings indicate adequate feasibility and acceptability of group CFT for TRD in Japanese clinical settings. Clinical trial registration: UMIN 000028698.